The Role and Evolution of Central Authorities - Paul Frijters; Alexander F. Tieman (Tinbergen Institute, 1999)
In this paper we argue that authorities aid cooperation by means ofdirect coordination or the enforcement of re-commitment devices suchas contract laws.Credible threats of violence allow this role. In alocal interaction model, an authority forms if mutually connected individuals with sufficient combined punishment potential have signalled their willingness to form such an authority, conditional upon the willigness of others todo so. Given a specific timing of decisions, we analyse the conditions under which authorities arise and under which they evolve into a stationary state with only one or several remaining authorities.
Keywords: B25; C7; D62; D70; H1; H4; 330; Central Authorities; Cooperation; Evolution; Externalities; Local Interaction; Theorie; Staatstheorie